EYE INFECTIONS THAT ARE COMMON IN INFANCY (Academicia Globe: Inderscience Research, 2023)
Chlamydia trachomatis was first isolated from the eyes of an infant with neonatal conjunctivitis in 1959. The organism could also be recovered from the uterine cervix of the mother of an infected infant. Inoculation of volunteers with the isolated agent caused clinical signs similar to acute trachoma with typical cellular inclusions. Inclusion conjunctivitis in newborn babies has been known since the first decade of this century and was called inclusion blenorrhea by Lindner. It is now recognised that C. trachomatis is one of the major causes of sexually transmitted diseases in industrialised countries. The infection can be transmitted to the infant at delivery when the mother is affected. The genital strains of C. trachomatis belong with few exceptions to one of the serogroups D through K. Classical trachoma in developing countries is associated with ocular strains generally belonging to the serotypes A through C. Neonatal chlamydial eye infection has been considered virtually nonexistent in areas with endemic trachoma like Egypt and Saudi Arabia. In Africa both neonatal chlamydial eye infection and classical trachoma have been observed in the same population,6 and recent reports indicate that neonatal chlamydial infection may be a substantial problem in different African countries.